INFLUENCE OF USER ACCEPTANCE ON THE PERFORMANCE OF ICT FIRMS IN NAIROBI COUNTY - Parrot, Yobera Hezekiah; Sang, Dr. Paul (European Journal of Business and Strategic Management, 2017)
Purpose: To determine how user acceptance influences the performance of ICT firms in Nairobi County. Methodology: This study utilized descriptive quantitative research design with a and is a cross- sectional survey. Multi-linear regression model was used in testing the study hypotheses. One or more of the Chief Officers in the target population was 486 ICT firms were the respondents. The primary data collection instrument was a structured questionnaire. From the data obtained descriptive and inferential statistics were extracted using SPSS and presented in respective tables. Results: The study found that there is no statistically significant influence of User acceptance on the performance of ICT firms in Nairobi County. Unique contribution to theory, practice and policy: Since no statistically significance relationships were found between User acceptance, attention should be put on information systems improving process rather than the direct influence of performance this study recommends that firms should determine benefits other than the overall firm's performance upon which the resource allocation argument can be based. This would avoid the risk of having stakeholder expectations that cannot be matched by outcomes.